Dark Sky Protection for Space Sustainability and Space Exploration - Yana Yakushina (Advanced Space Law, 2023)
Increased levels of artificial light at night (ALAN) have resulted in ground-based light pollution. The disappearance of the natural dark sky impacts various domains, including astronomy, environment, biodiversity, human health, energy efficiency, and climate. Concurrently, the recent influx of satellites into Earth’s orbit compounds the issue, by introducing orbital light pollution and further compromising nighttime visibility. This article briefly introduces the issue of light pollution and discusses the relationship between dark sky protection, the space environment, and the realm of space exploration. Recognizing the growing significance of preserving dark skies for different fields, the paper elucidates the important role of dark sky protection in ensuring space sustainability.